Animal Models of Ophthalmic Diseases - Chan, Chi-Chao (Essentials in Ophthalmology, 2016)
This book describes experimental animal models that mimic common human ocular diseases: herpetic keratitis, cataract, glaucoma, age-related macular degeneration, diabetic retinopathy, uveitis, retinitis pigmentosa, Graves' disease, and intraocular tumors.  In conjunction, these models reflect the diversity and utility of tools used to study human disease.  World expert clinicians discuss each model based on their clinical experience, and the text is supported by numerous photos and diagrams.  Development of suitable experimental models is critical in identifying risk factors for disease, elucidating fundamental molecular mechanisms in disease progression, and providing guidance as to whether or not a particular treatment is safe and effective for humans. Like other forms of medical research, ophthalmology and vision research focuses on the investigation of disease pathogenesis and the discovery of novel therapies through in vitro and in vivo methodology.  The in vivo experiments employ animal models including vertebrates (zebrafish, rodents, rabbits, and primates) and invertebrates (fruit flies and nematodes) for drug screening. In describing the most pertinent animal models of ophthalmic diseases, this book will be of interest to ophthalmologists, vision researchers, fellows, residents, and medical students.